A Comparison of the Reconstruction of Zakat Collectors’ Rights: Comparative Analysis of MUI Fatwa No. 8/2011 and Irsyad Fatwa No. 168/2022 Regarding the Operational Deficit of Zakat Institutions - Annisaa Hakim; Mohamad Athoillah; Fathimah Madaniyyah; Fahmi Hasan Nugroho (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2026)
Zakat collection agencies in Indonesia and Malaysia face operational deficits due to limitations on the rights of zakat collectors, even though zakat collection continues to increase. This study aims to compare MUI Fatwa No. 8 of 2011 and the Federal Territory Mufti’s Irsyad al-Fatwa No. 168 of 2022 regarding the limitations on the rights of zakat collectors. Using a normative qualitative approach with descriptive-analytical methods and literature review, the analysis is framed by the theories of Maqasid al-Sharia and Maslahah Mursalah. The results show that the MUI Fatwa emphasizes flexibility without fixed limits to adapt to operational contexts, while the Irsyad Fatwa strictly limits the fee to 1/8 to uphold the trust in accordance with the Shafi’i school of thought. These differing approaches impact operational efficiency and public trust: flexibility enhances efficiency but requires strict oversight, while rigid restrictions build trust but hinder institutional performance. This study enriches the discussion on contemporary fiqh muamalah and offers policy recommendations for sustainable zakat management.